Utilisation of Gabus Fish (Channa striata) In The Making Of Noodles As A Source Of Health Food - Wintah, Wintah; Kiswanto, Kiswanto (Universitas Teuku Umar, 2024)
noodles are a fast food high in carbohydrates and low in omega-3 fatty acids. Therefore, using snakehead fish which contains albumin and essential amino acids, fats, especially essential fatty acids, minerals, especially zinc (Zn), and several vitamins such as vitamin A, vitamin B, omega-3 fatty acids, sodium, and phosphorus, is a new innovation to create high-nutrient noodles. This community service aims to educate the public about the importance of consuming healthy food, one of which is by utilizing snakehead fish as a nutritious food source. The method used is a direct practice of making snakehead fish noodles.